Shariah scholars' view point on the practice of underwriting and risk rating for family takaful model - Htay, Sheila Nu Nu; Syed, Ahmed Salman; Mohammad , Khalid Jawahir (Canadian Center of Science and Education, 2013)
The practice of underwriting and risk rating for individual participants in family takaful stems from the underwriting practice in life insurance, and thus could contain elements which contravene the essence of the Shari’ah. A review of literature on takaful indicates that there are very few materials which look at the underwriting practice from a Shari’ah perspective. The objective of this study is to find out the Shari’ah viewpoint on the underwriting and risk rating practice for individual participants in family takaful. The study sample consists of five purposefully selected Shari’ah experts on takaful. The research method uses is based on the Delphi technique. This study found that most of the Shari’ah scholars interviewed did not seem to have a deep exposure to the underwriting and risk rating practice in family takaful. They however declare that underwriting and risk rating is permissible, although they had some concerns regarding some of the factors use in the underwriting process. The findings of this study will be of interest to the Shari’ah scholars, takaful operators, regulatory bodies, academicians, and other stakeholders.